Three-Dimensional Reconstruction of Space Targets Utilizing Joint Optical-and-ISAR Co-Location Observation - Wanting Zhou; Lei Liu; Rongzhen Du; Ze Wang; Ronghua Shang; Feng Zhou (Remote Sensing)
With traditional three-dimensional (3-D) reconstruction methods for space targets, it is difficult to achieve 3-D structure and attitude reconstruction simultaneously. To tackle this problem, a 3-D reconstruction method for space targets is proposed, and the alignment and fusion of optical and ISAR images are investigated. Firstly, multiple pairs of optical and ISAR images are acquired in the joint optical-and-ISAR co-location observation system (COS). Then, key points of space targets on the images are used to solve for the Doppler information and the 3-D attitude. Meanwhile, the image offsets of each pair are further aligned based on Doppler co-projection between optical and ISAR images. The 3-D rotational offset relationship and the 3-D translational offset relationship are next deduced to align the spatial offset between pairs of images based on attitude changes in neighboring frames. Finally, a voxel trimming mechanism based on growth learning (VTM-GL) is designed to obtain the reserved voxels where mask features are used. Experimental results verify the effectiveness and robustness of the OC-V3R-OI method.